2015
DOI: 10.1016/j.cell.2015.09.032
|View full text |Cite
|
Sign up to set email alerts
|

A One Precursor One siRNA Model for Pol IV-Dependent siRNA Biogenesis

Abstract: SUMMARY RNA-directed DNA methylation in Arabidopsis thaliana is driven by the plant-specific RNA Polymerase IV (Pol IV). It has been assumed that a Pol IV transcript can give rise to multiple 24-nucleotide (nt) small interfering RNAs (siRNAs) that target DNA methylation. Here, we demonstrate that Pol IV-dependent RNAs (P4RNAs) from wild-type Arabidopsis are surprisingly short in length (30-to-40 nt) and mirror 24-nt siRNAs in distribution, abundance, strand bias, and 5’-adenine preference. P4RNAs exhibit trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
319
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(345 citation statements)
references
References 45 publications
19
319
1
Order By: Relevance
“…Of the 4 464 > 24 nt P4 RNA clusters identified in dcl1/2/3/4 mutant plants, we found that 1 751 overlap with DRM2-dependent (D2) loci and 651 overlap with CMT2-dependent (C2) loci, and 73 overlap with both D2 and C2 loci, consistent with the findings that both D2 and C2 loci produce 24-nt siRNAs [13,32]. During the preparation of this manuscript, two independent groups reported short, Pol IV-dependent precursors of 24-nt siRNAs [58,59], which corroborate our results.…”
Section: Discussionsupporting
confidence: 71%
“…Of the 4 464 > 24 nt P4 RNA clusters identified in dcl1/2/3/4 mutant plants, we found that 1 751 overlap with DRM2-dependent (D2) loci and 651 overlap with CMT2-dependent (C2) loci, and 73 overlap with both D2 and C2 loci, consistent with the findings that both D2 and C2 loci produce 24-nt siRNAs [13,32]. During the preparation of this manuscript, two independent groups reported short, Pol IV-dependent precursors of 24-nt siRNAs [58,59], which corroborate our results.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, it has only been recently revealed that single 24-nucleotide siRNAs are produced by DCL3-mediated processing of a single short precursor, 27 to 50 nucleotides in length, generated by PolIV and RDR2 and referred to as P4R2 RNA (Blevins et al, 2015;Zhai et al, 2015). Because 24-nucleotide siRNAs coincide with P4R2 RNAs at either their 59 or 39 end, these short precursors likely are cut once by DCL3 to generate a single siRNA.…”
Section: Rtl2 Likely Cleaves a Subset Of Poliv-rdr2-dependent Dsrnasmentioning
confidence: 99%
“…Because 24-nucleotide siRNAs coincide with P4R2 RNAs at either their 59 or 39 end, these short precursors likely are cut once by DCL3 to generate a single siRNA. Although this model explains the biogenesis of most 24-nucleotide siRNAs, the authors wondered if a yet to be identified RNaseIII was at play between the biosynthesis of some P4R2 RNAs by PolIV and RDR2 and their processing by DCL3 (Zhai et al, 2015). At the whole-genome level, reads 27 to 50 nucleotides in length, which likely are P4R2 RNAs, overaccumulate in dcl234, but not in rtl2 ( Figure 4A), ruling out that all the reads >26 nucleotides detected in dcl234 could be RTL2 products.…”
Section: Rtl2 Likely Cleaves a Subset Of Poliv-rdr2-dependent Dsrnasmentioning
confidence: 99%
“…dsRNAs are then processed by DCL3 to produce 24-nucleotide hc-siRNAs (Xie et al, 2004). Recent studies suggest that Pol IV/RDR2 products are mainly 30 to ;40 nucleotides in length and on average only one siRNA could be produced from each precursor (Blevins et al, 2015;Zhai et al, 2015b). hc-siRNAs are exported into the cytoplasm, where they are loaded into AGO4, and mature AGO4/siRNA complexes are selectively transported into the nucleus, which may provide a regulatory point prior to the effector stage of RdDM (Qi et al, 2006;Ye et al, 2012).…”
Section: Dna Methylationmentioning
confidence: 99%